1998
DOI: 10.1093/ejo/20.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Frictional forces related to self-ligating brackets

Abstract: SUMMARY Orthodontic tooth movement can be regarded as teeth sliding on a wire like pearls on a string, the force being supplied by springs or elastics. The movement implies friction between wire and bracket, taking up part of the force and leaving an uncontrolled amount to act on the teeth. The friction is likely to depend on bracket construction and wire material. Therefore, in this investigation the friction of self-ligating brackets and beta-titanium wires was evaluated, as opposed to more conventional conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
1
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(142 citation statements)
references
References 27 publications
6
116
1
11
Order By: Relevance
“…It allows for passive trapping of the wire (except in the interactive brackets with larger diameter wires) without the involvement of any outside connecting agent and allows the use of lighter forces due to reduced friction, which helps to preserve the anchorage 3,9,10,14,17,18,21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It allows for passive trapping of the wire (except in the interactive brackets with larger diameter wires) without the involvement of any outside connecting agent and allows the use of lighter forces due to reduced friction, which helps to preserve the anchorage 3,9,10,14,17,18,21 .…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to consider that during canine retraction, the lower the rate of friction, the lower will be the requirement of the anchorage elements. When the frictional resistance was compared between self-ligating brackets using beta-titanium and stainless steel wires in round and rectangular configurations, the round wire produced less friction than the strength of rectangular wires, and the betatitanium wires showed markedly more friction than the steel wires 14 . It has also been demonstrated that increasing the angle produced a greater amount of friction, and self-ligating brackets showed less friction than conventional types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a 0.021 x 0.025" wire, the SPEED bracket produced significantly greater friction than either the Mobil-Lock or Activa brackets. In a similar study, Pizzoni et al,1998, compared the Damon SL bracket to the SPEED bracket with an active clip and two conventionally ligated brackets. The two self-ligating brackets were not statistically different for a 0.018" wire, but when 0.017 x 0.025" wires were used, the active clip on the SPEED bracket produced significantly greater friction than the passive Damon bracket.…”
Section: Active Vs Passive Self-ligating Bracketsmentioning
confidence: 99%
“…[4][5][6] Damon described the clinical use of his Damon brackets and proposed that this low friction is a major factor in enabling more efficient treatment. 7 However, the assumption has been made that along with low friction in vitro, comes more rapid alignment and a reduction in treatment time in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%